Implementation Of Digital Marketing On Wardah Consumer Satisfaction In Tiktok Shop (Case Study Of Management Study Program Students, 2021, Panca Budi Development University) - Luthvia Aulia; Dewi Nurmasari Pane; Nurafrina Siregar (Jurnal Fokus Manajemen, 2026)
This study aims to analyze the influence of company size, profitability, free cash flow, and liquidity on debt policies in cosmetics and household goods sub-sector companies listed on the Indonesia Stock Exchange for the period 2020–2024. This study uses a quantitative approach with a panel data regression method on 5 companies. The selection of the panel data regression model was carried out through the Chow Test and the Hausman Test, which showed that the Fixed Effect model was the most appropriate model to use. The results of the study show that simultaneously company size, profitability, free cash flow, and liquidity have a significant effect on debt policy. Partially, profitability and liquidity have a negative and significant effect on debt policy, while company size and free cash flow have no significant effect. The value of the determination coefficient showed that 77.15% of the variation in debt policy could be explained by independent variables in the model, while the rest was influenced by other factors outside the study.